Enhanced gypsum boards with activated carbon composites 2 and phase change materials for advanced thermal energy 3 storage and EMI shielding properties - Ikram, Rabia; Karakassides, Michael A.; Gioti, Christina; Vasilopoulos, Konstantinos C.; Baikousi, Maria; Salmas, Constantinos E.; Ntaflos, Angelos; Paipetis, Alkiviadis S.; Viskadourakis, Zacharias; Agathopoulos, Simeon; Kenanakis, George (Multidisciplinary Digital Publishing Institute, 2024)
This work presents the development of novel gypsum board composites for advanced thermal energy storage (TES) and electromagnetic interference (EMI) shielding applications. Activated carbon (AC) derived from spent coffee with a high surface area (SBET = 1372 m2/g) was used as a shape stabilizer, while the commercial paraffin, RT18HC, was used as organic encapsulant phase change material (PCM). The AC showed a remarkable encapsulation efficiency as a shape stabilizer for PCM, with ~120.9 wt% (RT18HC), while the melting enthalpy (∆Hm) of the shapestabilized PCM was 117.3 J/g. The performance of this PCM/carbon nanocomposite as a thermal energy storage material was examined by incorporating it into building components, such as gypsum wallboards. The microstructure of these advanced panels, their density, and their dispersion of additives were examined using X-ray microtomography. Their thermal-regulated performance was measured through a self-designed room model with a similar homemade environmental chamber that was able to create a uniform temperature environment, surrounding the test room during heating and cooling. The measurements showed that the advanced panels reduce temperature fluctuations and the indoor temperature of the room model, in comparison with normal gypsum panels, by a range of 2–5%. The investigated gypsum board composite samples showed efficient electromagnetic shielding performance in a frequency range of 3.5–7.0 GHz, reaching an EMI value of ~12.5 dB, which is adequate and required for commercial applications, when filled with PCMs.